PENGAWASAN PEMANFAATAN TATA RUANG KOTA PEKALONGAN - Aliffianti Bhara Timor; Ida Hayu Dwimawanti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Supervision of the utilization of spatial is a business activity to control the implementation of the spatial utilization in accordance with the plan agreed upon earlier. This surveillance is necessary because if a space in an area isn’t used properly and do not comply with it should it will negatively impact to the environment and if a spatial utilization in a certain area is used in accordance with the allocation area the it will impact both for the surrounding environment. With regard to the utilization of space. The city of Pekalongan is still not good and it has some negative impacts such as floods and the narrowing of the road. This oversight ensures implementation of the utilization of spatial plan which the government had already agreed. The plan is on Local Regulations No 30 in 2011 about Spatial Plan area of Pekalongan in 2009-2029. This research uses descriptive research methods with qualitative approaches. The result of this study supervision of the utilization of spatial in Pekalongan by using the theory of management, which are the determination of standard of supervision, monitoring, evaluation and corrective action. This surveillance is technically done by Spatial Department of public works city of Pekalongan. Supervisors who supervise the utilization of spatial consist four people who are divided in to the four regions and the amount is not enough because each region has a different wide. In addition the obstacles of this surveillance are the lack of socializing frequency and nit-on-the target socialization. If at the time of the supervision there is a violation done and it can be proven, it will be given administrative sanctions in accordance with sanctions. The inventory of the infringement is also still lacking. DPU Pekalongan should increase the number of supervisors in district that has a larger area. Socialization also needs to be held periodically throughout the year. Every infringement should be noted well up to the results of the act ss material for future evaluation